The Integration Of Religious Values Into Sciences-Related Topic Toward Postmodernism Of Science In Islam - Wedra Aprison; Juanaidi Junaidi (AL-ISHLAH: Jurnal Pendidikan, 2022)
For a long time, Islam has a dichotomy tradition of science and religion. As a result of the Dutch colonialism, dual education and curriculum systems were born in Indonesia, namely the education system of the ministry of national education which was often considered as a secular curriculum and the education system of the ministry of religion which considered less in science aspect. The democratization era provides opportunity to synthesize them with the advent of Integrated Schools of Islam as an alternative. This research aims to find out how the integration of Islam values into science. The qualitative method is used as research methodology. The data were collected through observation, in-depth interview, and documentation. The result of the research reveals that the school not only teaches the science, but also the fact behind the fact. They integrate science and spiritual values of Islam. The integration is done by synthesizing two curriculums into one curriculum of Integrated Elementary School of Islam. It is a great effort towards the synthesis of postmodernism of science in Islam.